Qualitative Analysis of Knowledge of Manager Nurses about Restraint Practices - Türkan Karaca; Semiha Aydın Özkan (Association of Nurse Managers, 2018)
INTRODUCTION: This study was conducted to evaluate the knowledge of manager service/ICU nurses about physical and chemical restraint practices. METHODS: In this study, a descriptive phenomenological method was used based on the concept of "restraint". The concept of restraint was considered as physical restraint and chemical restraint. The study was conducted with general service/ıntensive care units manager nurses at a Research Hospital. The analysis of the data was done in 4 steps using Giorgi's (1997a; 2000b) phenomenological method analysis. RESULTS: The average age of the manager nurses was 32,57 +- 6,36 and the average of the total working years was 9,73 +- 6,18. According to the expressions of the manager nurses, two hours, benefit, patient safety, fastening, doctor-nurse, verbal and written permission, speaking and helping themes were appeared. DISCUSSION AND CONCLUSION: In this study, it was determined that manager nurses stated that they used restraints by reasons such as not harming the patient, benefiting, patient safety. It should not be forgotten that despite the fact that the restraint procedure is for the benefit of the patient, this procedure restricts the patient's freedom and has complications that may reach to death.